2022
DOI: 10.31744/einstein_journal/2022ao6599
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of 68Ga-PSMA PET-CT and PET-MRI in lymph node staging for localized prostate cancer

Abstract: Objective: To evaluate the predictive value of positron emission computed tomography or magnetic resonance (PET-CT and PET-MRI) using gallium-68-labeled prostate-specific membrane antigen ( 68 Ga-PSMA) in lymph node involvement in prostate cancer. Methods: A retrospective study comprising 91 patients diagnosed with prostate cancer between 2016 to 2020, who underwent 68 Ga-PSMA PET-CT or PET-MRI for staging before prostatectomy. The patients were divided into Group 1, with 65 patients with satisfactory patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In another study by Kubilay et (19). Two recent retrospective studies and a literature review reached the same conclusion regarding the utility of Ga-68-PSMA-PET/CT scan in detecting lymph node metastases of prostate tumors (20)(21)(22).…”
Section: Discussionmentioning
confidence: 64%
“…In another study by Kubilay et (19). Two recent retrospective studies and a literature review reached the same conclusion regarding the utility of Ga-68-PSMA-PET/CT scan in detecting lymph node metastases of prostate tumors (20)(21)(22).…”
Section: Discussionmentioning
confidence: 64%
“…The authors also concluded that Ga-68-PSMA-PET/CT scan had high speci city and accuracy for detecting lymph node metastasis (96.5% and 84.5%, respectively), but its sensitivity was relatively low (30.6%) (19). Two recent retrospective studies and a literature review reached the same conclusion regarding the utility of Ga-68-PSMA-PET/CT scan in detecting lymph node metastases of prostate tumors (20)(21)(22).…”
Section: Discussionmentioning
confidence: 79%
“…While there are significant diagnostic and therapeutic advantages to these findings not previously studied with respect to prostate biopsies alone, which includes avoidance of active surveillance and possibly focal therapy and perhaps calling for an aggressive lymph node dissection, it is important to consider that the relatively high false negative detection rate of IDC/Crib in biopsies may affect treatment outcomes significantly. Additionally, the accuracy of PSMA PET–CT for lymph node staging of prostate cancer is 86.5% (95% CI 0.74-0.94; P = .06) with sensitivity of 58.3% and specificity of 95%, 4 which although highly acceptable for clinical decision-making, does raise a concerning question for possible overdiagnosis and therefore does not equate to tissue-based diagnosis. In fact, the only cohort of patients who actually went on to have radical prostatectomy and were included in this study had no statistically significant correlation with the presence of IDC/Crib finding on prostate biopsy.…”
mentioning
confidence: 99%